Long-term nitrogen and tillage effects on soil physical properties under continuous grain sorghum - Presley, DeAnn R.; Sindelar, Aaron J.; Buckley, Meghan E.; Mengel, David B. (My University, 2013)
Grain sorghum [Sorghum bicolor (L.) Moench] is an important grain crop grown in both highly productive and marginal areas in the central Great Plains because of the crop’s ability to utilize the erratic precipitation observed in this region. More effective capture and storage of this limited rainfall is needed to improve the productivity and profitability of dryland agriculture. The objective of this study was to determine the effects of long-term tillage and nitrogen (N) fertilization on soil physical and hydraulic properties after long-term continuous grain sorghum production. Variables included conventional tillage (CT) and no-till (NT) and four rates of N fertilizer. Selected soil quality indicators included soil organic carbon (SOC), bulk density (BD), wet aggregate stability (WAS), and ponded infiltration. No-till accumulated more SOC in the surface 0-5 cm, and was less dense at all depths than CT. When tillage was compared across all N rates, NT contained 30% greater SOC than CT at the 0-5 cm. Mean weight diameter (MWD) was larger with increasing N fertilization and eliminating tillage. Ponded infiltration rates were greatest for the high N fertilization rate under NT, and lowest for the 0 Kg N haˉ¹ rate under CT. In this long-term grain sorghum system, increasing N fertilization rate and NT both positively affected soil physical properties. These improvements in hydraulic properties will aid in more effectively capturing unpredictable precipitation, and further underscore the utility of NT management practices for the central Great Plains region.
Citation: Presley, DeAnn, Aaron Sindelar, Meghan Buckley, and David Mengel. "Long-Term Nitrogen and Tillage Effects on Soil Physical Properties under Continuous Grain Sorghum." Agronomy Journal 104.3 (2012): 749-55. https://doi.org/10.2134/agronj2011.0311
Keywords: Grain sorghum; Sorghum bicolor (L.) Moench.; Tillage; Nitrogen fertilization; Soil physical properties